Advancing tendon regeneration through the development of bio-stimulating tissue engineering approaches - Gomes, Manuela E. (2015)
Tendon tissue engineering (TE) requires tailoring scaffolds designs and properties to the anatomical and functional requirements of tendons located in different regions of the body. Cell sourcing is also of utmost importance as tendon cells are scarce. Recently, we have found that it is possible to direct the tenogenic differentiation of Amniotic fluid and Adipose tissue derived stem cells (hAFSCs and hASCs), and also that there are hASCs subpopulations that might be more prone to tenogenic differentiation. Nevertheless, biochemical stimulation may not be enough to develop functional TE substitutes for a tissue that is known to be highly dependent on mechanical loading.